2022
DOI: 10.33963/kp.a2022.0150
|View full text |Cite
|
Sign up to set email alerts
|

Culprit plaque location within the left circumflex coronary artery predicts clinical outcomes in patients experiencing acute coronary syndromes with percutaneous coronary intervention: Data from the ORPKI registry

Abstract: Background:The left circumflex (LCx) artery is the most diagnostically challenging of the coronary branches in terms of diagnostics because the clinical presentation and electrocardiography (ECG) do not always suggest critical occlusion despite its presence. Therefore, it is important to determine the factors contributing to the clinical manifestation and outcome, such as the culprit location. Aims:To determine the relationship between the location of the culprit plaque and clinical outcomes in the LCx artery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Ayad et al (2021) expanded upon this finding by showing that the incidence of in-hospital arrhythmia was considerably higher among NSTEMI with an occluded culprit artery compared to NSTEMI without a an occluded culprit artery (Ayad et al 2021). Given the connection between left circumflex artery occlusion and NSTEMI with an occluded culprit artery, one previous study reported that NSTEMI patients with an occluded culprit left circumflex artery were more likely to suffer cardiac arrest and even higher mortality compared to STEMI (Chyrchel et al 2022). However, when evaluating long term outcomes, Kos et al (2021), with a median follow-up of 4.7 years, reported that the presence of a an occluded culprit artery, regardless of STEMI or NSTEMI presentation, was not associated with a higher long-term mortality; however, NSTEMI was associated with a higher mortality rate compared with STEMI, independent of angiographic presentation (Kos et al 2021).…”
Section: Patient Outcomesmentioning
confidence: 99%
“…Ayad et al (2021) expanded upon this finding by showing that the incidence of in-hospital arrhythmia was considerably higher among NSTEMI with an occluded culprit artery compared to NSTEMI without a an occluded culprit artery (Ayad et al 2021). Given the connection between left circumflex artery occlusion and NSTEMI with an occluded culprit artery, one previous study reported that NSTEMI patients with an occluded culprit left circumflex artery were more likely to suffer cardiac arrest and even higher mortality compared to STEMI (Chyrchel et al 2022). However, when evaluating long term outcomes, Kos et al (2021), with a median follow-up of 4.7 years, reported that the presence of a an occluded culprit artery, regardless of STEMI or NSTEMI presentation, was not associated with a higher long-term mortality; however, NSTEMI was associated with a higher mortality rate compared with STEMI, independent of angiographic presentation (Kos et al 2021).…”
Section: Patient Outcomesmentioning
confidence: 99%